2013
DOI: 10.2304/gsch.2013.3.2.163
|View full text |Cite
|
Sign up to set email alerts
|

For Adults Only? Young People and (Non)Participation in Sexual Decision Making

Abstract: The term 'participation' is often used to refer to children and young people's involvement in decision-making processes but it also denotes the individual decisions that they make about their everyday lives. With regards to sexuality, children and young people are routinely excluded from policy formation and decision-making processes, due to assumptions about their sexual immaturity and lack of competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The works of Sigmund Freud mark a new era of understanding child sexuality and Freud has been commonly credited for "inventing" childhood sexuality (Egan and Hawkes, 2008). As a result, 20th century scholars and experts from various fields and disciplines began to use their corresponding expertise to publicly and explicitly acknowledge child sexuality as a normal and natural reality (Angelides, 2004) and adults began to exercise considerable power over children to determine the time at which children are deemed to be sexual and decide what knowledge they pass to children about sex (Moore, 2013). Although Fishman's periodization provided an important perspective for understanding the changing conceptualizations of childhood sexuality in history, it was constructed at the beginning of 1980s and missed various surging social movements and other new development since then.…”
Section: The History Of Childhood Sexualitymentioning
confidence: 99%
“…The works of Sigmund Freud mark a new era of understanding child sexuality and Freud has been commonly credited for "inventing" childhood sexuality (Egan and Hawkes, 2008). As a result, 20th century scholars and experts from various fields and disciplines began to use their corresponding expertise to publicly and explicitly acknowledge child sexuality as a normal and natural reality (Angelides, 2004) and adults began to exercise considerable power over children to determine the time at which children are deemed to be sexual and decide what knowledge they pass to children about sex (Moore, 2013). Although Fishman's periodization provided an important perspective for understanding the changing conceptualizations of childhood sexuality in history, it was constructed at the beginning of 1980s and missed various surging social movements and other new development since then.…”
Section: The History Of Childhood Sexualitymentioning
confidence: 99%
“…Determining how to deliver relationships and sex education (RSE) according to “rights-based” principles is subject to current debate within the field. Rights-based RSE is a contested concept (Moore, 2013 ). It has been variously conceived of as the right to receive RSE and the right to sexual health and well-being, as well as in terms of the teaching approach and pedagogical style that frames the delivery of RSE content.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that teaching and informing young people about their rights is beneficial for skill development and helps prepare young people for participation as productive citizens in a democratic society (Goldman, 2008 ; Levesque, 2000 ). RSE is, therefore, often advanced as a “public good.” Given that conceptualizations of what is “good” and “appropriate” for young people remain contested, however, so too does the nature of RSE (Moore, 2013 ). Different forms of RSE thus remain despite a broad consensus that young people have a right to education about sex and relationships.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations